Evolution of Operations Management Research: from Managing Flows to Building Capabilities. Issue 10 (25th June 2020) - Zhang, Fuqiang; Wu, Xiaole; Tang, Christopher S.; Feng, Tianjun; Dai, Yue
Abstract : This forum study examines the past and the future of Operations Management (OM) research. First, we investigate the evolution of OM research from 1997 to 2018 by using machine learning tools to analyze all OM papers published in five journals (JOM, MS, M&SOM, POM, and OR), and find that the number of information/financial flow‐focused OM research papers has increased steadily over the years. Second, we present three research topics motivated by the US‐China trade war and the Covid‐19 pandemic, and postulate that future OM research is likely to involve all three flows: material, information, and financial flows. Finally, we argue that, to achieve operational efficiency, resilience, and sustainability in the Industry 4.0 era, firms should build (or strengthen) three new capabilities: Connectivity, Clarity, and Continuity . As firms develop new ways to build these new capabilities, more innovative OM research ideas will ensue.